PENGEMBANGAN E-LKPD PERKALIAN BERBASIS NUMERASI UNTUK SISWA KELAS 3 SEKOLAH DASAR - Fina Ika Siswardani; Wahyuningtyas , Dyah Tri; Sesanti, Nyamik Rahayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Students have difficulty grasping the concepts of multiplication and numeracy due to a lack of interactive teaching materials related to everyday life. This study aims to develop an Electronic Student Worksheet (E-LKPD) based on numeracy for teaching multiplication to third-grade elementary school students. The research employed a Research and Development (R&D) method using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Data analysis was conducted using both qualitative and quantitative methods. Data collection instruments included validation sheets from material and media experts, student response questionnaires, and interviews. The validation results assessed feasibility, the student questionnaire measured practicality, and the pre-test and post-test evaluated effectiveness. Validation showed a high level of feasibility, with scores of 85% from material experts, 89% from media experts, and 89% from language experts, categorized as very feasible. The pre-test and post-test results showed an improvement of 20 points, with an average N-gain of 0.69, classified as moderate. Student responses reached 92.26%, indicating a very positive reception. These findings suggest that the E-LKPD effectively enhances students' understanding of multiplication concepts through a contextual numeracy approach. Therefore, the E-LKPD is suitable to be used as an alternative mathematics learning media to support the improvement of numeracy literacy for third-grade elementary students.